(3SdGaI GdYUQ aj eMGSf CYjGf GdYUQs - (3Ydj NGf Hf fXGe GdOjf CMeO Hf eYUhe GdOTJcj GdTjQGRj,J (B1117 (3g` s
(3ChdgG (B:s
(3GdTjN LeGd GdOjf eMeO Hf YjO GdfMai GdeGdci ef ChdGO eGdc GdfSH GdGTJQi hGdGOH GdHMJQi s
(3BNQgG (B:s
(3hdg CYRg Gddg ai GdOGQjf ai GdZRd hUa NWhH Gdghi aCeG Qb dgG bdHgG hdGfG acf HGSei hdGJUQM hbd CUGH GdQOF adGfG s
(3HBNQgG eLehYI edMbGJ edMbGJ GdSdGaI gPg GdedMbGJ cJHJ ai fgGjI GdfSNI GdeDQNI SfI (B1221 (3hdYdgG ef JCdja eDda GdSdGaIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B20s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdCOHs